Significance Performance Analysis On The Quality Of University Administrative Services - Pratiwi, Candra; Noor, Irwan; Rozikin, Mochammad (Universitas Padjadjaran, 2024)
Administrative services refer to kind of service that cannot be separated from activities in higher education that are often utilized by students. From the beginning of enrolment to graduation, administrative activities are certainly inevitable for students. The main purpose of this research is to analyze the level of importance and performance of the quality of administrative services in higher education implemented at the Faculty of Administrative Sciences, Universitas Brawijaya. The method used is quantitative method with survey research type. The population sampling was 4,164 students, then based on the Krejcie & Morgan sampling technique, a sample size of 354 students was obtained. Data collection was carried out by distributing questionnaires and processed according to the results which were then tabulated in the Importance Performance Analysis quadrant. The results of this study are: (1) Registration effectiveness dimensions and registration and financial aid effectiveness dimensions are in accordance between interests and performance; (2) Student-centered dimensions and excellent service dimensions are considered less important by students and their performance is still lacking; (3) Academic service dimensions are considered less important by students and their performance is excessive; (4) The requirement for continuous monitoring and evaluation of staff in charge of administrative services.